ANALISIS KETIMPANGAN INVESTASI ANTAR PROVINSI DI PULAU SUMATERA DAN KALIMANTAN TAHUN 2005-2013 - Sisca Hermayeni; Hendro Ekwarso; Dahlan Tampubolon (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to analyze the Inter-Provincial Investment Disparities in Sumatra and Kalimantan. Where will the results of this study can be seen for what disparities. In addition to knowing imbalance occurs between regions or inter-region. The analysis used in this study is a qualitative analysis based on the theory as well as the opinions of experts who are already applicable to the public. The formula used in this research that Williamson index and Theil entropy index. From the calculation results obtained during the observation period (2005-2013) to the island of Sumatra and Kalimantan Island as follows: the average DDI and FDI imbalance Sumatra, DDI and FDI Kalimantan by using IW during the observation period (2005 -2013) are 0.0182, 0.0067, 0.0139, and 0.0055. Disparities average investment by Entropi Theil index for DDI and FDI Sumatra, DDI and FDI Kalimantan during the observation period (2005-2013) are 0.3204, 0.3403, 0.3598, and 0, 3258. By using the index calculation Williamson DDI disparities is greater than FDI. While using the Theil entropy index calculation DDI greater disparities occurs on the island of Kalimantan Island with a value of 0.3598 and FDI greater disparities occurred in Sumatra with a value of 0.3403. By looking at the average of the two regions Williamson index then we can conclude that the disparities of investment tends to be higher in Sumatra than on the island of Kalimantan.Keywords: investment, population, investment imbalances, Williamson index, Theil entropy index